Pengaruh Pelatihan Tehnik Menyusui Yang Benar Pada Ibu Nifas Primipara Terhadap Ketrampilan Dalam Menyusui - Triwik Sri Mulati; Dewi Susilowati (Interest : Jurnal Ilmu Kesehatan, 2016)
Abstract: The Right Breastfeeding Techniques, Postpartum Primiparous. The purpose of this study was to prove the influence of breastfeeding technique training right at the primiparous postpartum mother breastfeeding skills. This type of research is a Quasi-Experimental. Samples are 20 primiparous postpartum mothers in the district of Klaten. Sampling technique is purposive consecutive sampling. Analysis of the data used in this research is to test the Wilxocon. The results of this study are the test results Wilxocon between data pretest and post-test 1 shows the p-value = 0.000, where p <0.05 which means there is a significant difference between the value of the skills puerperal women primipara before and after given one training technique of right breastfeeding, In addition test results Wilxocon between data posttest 1 and posttest 2 shows the p-value = 0.000, where p <0.05 which means there is a significant difference between the value of the skills postpartum mother primipara after given one training and after a given number of training courses on breastfeeding technique is correct. Therefore it can be concluded that the correct breastfeeding technique training has proven to improve the skills of breastfeeding on postpartum mother primipara